An empirical analysis of the Mexican term structure of interest rates - Josué Fernando Cortés Espada; Manuel Ramos-Francia; Alberto Torres García (Banco de México, 2008)
We study the dynamics of the term-structure of interest rates in Mexico. Specifically, we investigate time variation in bond risk premia and the common factors that have influenced the behavior of the yield curve. We find that term-premia in government bonds appear to be time-varying. We then estimate a principal components model. We find that over 95% of the total variation in the yield curve can be explained by two factors. The first factor captures movements in the level of the yield curve, while the second one captures movements in the slope. Moreover, we find that the level factor is positively correlated with measures of long-term inflation expectations and that the slope factor is negatively correlated with the overnight interest rate.
Keywords: C13; E43; G12; 330; Term-Structure; Time-Varying Risk Premia; Principal Components; Zinsstruktur; Mexiko